If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(n + 11) = 81 Reorder the terms: 7(11 + n) = 81 (11 * 7 + n * 7) = 81 (77 + 7n) = 81 Solving 77 + 7n = 81 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-77' to each side of the equation. 77 + -77 + 7n = 81 + -77 Combine like terms: 77 + -77 = 0 0 + 7n = 81 + -77 7n = 81 + -77 Combine like terms: 81 + -77 = 4 7n = 4 Divide each side by '7'. n = 0.5714285714 Simplifying n = 0.5714285714
| X+21.83=65.5 | | 5/9÷4/9 | | 8z+3-5z=3+2z-1 | | 12(n+-8)=36 | | (a^2)+7a+12=0 | | 4=0.1x-0.2x-2 | | 6x+212.85=2x+297.99 | | 0.5x-2=0.15x+5 | | 7(8+4+x)= | | Y=4x-b | | 91-166=-8(-4y)-17(2y)+y | | X=65.5 | | 5y^2-7=42 | | 3/4b=46.50 | | 45+20+0.55x=45+0.65x | | 5x+(4)(-5)=-20 | | 46.50b-3/4 | | n-20.64=-6.64 | | X+5x+y+3y+5-2= | | 600=m-12+m | | 7(-3x-1/7) | | 2.78=.6*x | | y-13=3(x-5) | | 5(n+-11)=-16 | | 49x^2+70x=25 | | x=60/100 | | h=-16t^2+11t+85 | | 10(4+-4)= | | 11x+9y=5 | | 0.99+36x=1.39 | | 0.99-36x=1.39 | | (4*3)+(4*x)=36 |